Theoretical and Applied Analysis of Narrator Evaluation by Imam Al-Bazzar in 'Al-Bahr Al-Zakhar - Darash, Abd al Razzaq Hasan (Journal of Islamic and Religious Studies, 2023)
The evaluation among narrators is one of the most essential and extensive aspects of the science of criticism and authentication, dealing with advanced stages in assessing the narrator and the narration. Imam Al-Bazzar, one of the scholars whose opinions are relied upon in criticism and authentication, significantly enriched this field through his compilation, "Musnad Al-Bazzar." This research aims to examine aspects of the subject from Imam Al-Bazzar's perspective, conducting a comprehensive study that elucidates the criteria for evaluation by Imam Al-Bazzar in his compilation, the categories of the assessment according to him, the reasons for selecting the narrators who underwent evaluation, followed by an empirical study. This study involves collecting the narrators evaluated by Imam Al-Bazzar in his compilation, studying them, analyzing the evaluations, and elucidating the justifications for his assessments. Additionally, a comparison is drawn between his and other scholars’ judgments.